Place, race and politics : the anatomy of a law and order crisis - Weber, Leanne (Emerald Publishing Limited, 2021)
Place, Race and Politicspresents an integrated analysis of the social and political processes that combined to construct a media-driven 'crisis' concerning African youth crime in the city of Melbourne, Australia.